Access and attitude of Internet use among college students - Morales Ramírez, Alejandra (2020)
This article proposes to identify the attitude and habitual practices of Internet access among university students, in addition to knowing their degree of relationship with age, gender, semester, career and academic performance. For this, a qualitative and correlational research model will be used through a sociodemographic questionnaire and the scale Telephone, tool, territory, information treasure and toy (5T). 813 students from a public university in Mexico participated. The use of the Internet is massive among university students, there are specific differences in the type of content they access. Men, participants enrolled in the second semester and those who are 21 years old score higher when they use the Internet to play and as entertainment compared to their peers. There is no relationship between Internet uses, age and academic performance. The implications of the results found are discussed.